A Paper in Health Sciences: The Student Mentor. (8th July 2015) - Romeu, Marta; Taltavull, Núria; Moragas, Carlota M; Valls, Rosa M; Ribé, Mireia; Tarro, Lucía; Farré, Jordi; Albina, M Luisa; Casajuana, M del Carme; Arija, Victoria; Solà, Rosa; Nogués, M Rosa; et al.
Abstract: Ethics and communication with patients are basic transversal skills for the Degrees in Medicine, Physiotherapy and Nutrition. In this model, senior students use video to create simulated clinical cases with ethics and communication components, and conduct academic mentoring using these cases. To ensure quality video recordings, the students are introduced to visual language by students of the Master's in Communication, thus completing the learning cycle.